2017
DOI: 10.1002/cne.24295
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and chemical composition of estrogen receptor β neurons in the paraventricular nucleus of the female and male mouse hypothalamus

Abstract: Activation of estrogen receptor beta (ERβ)-expressing neurons regulates the mammalian stress response via the hypothalamic–pituitary–adrenal (HPA) axis. These neurons densely populate the paraventricular nucleus of the hypothalamus (PVN). Recent research has revealed striking differences between rat and mouse PVN cytochemistry, but careful exploration of PVN ERβ neurons in mice has been hindered by a lack of specific ERβ antisera. Therefore, we used male and female transgenic mice expressing EGFP under the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 92 publications
(162 reference statements)
4
41
1
Order By: Relevance
“…Considering the low percentage of Esr2/CRF and Esr2/AVP in the parvocellular parts in the current study, further experiments are required to determine the indirect action of estrogens on the HPA through AVP and CRF neurons expressing Esr2. In contrast to this result, in mice, the number of CRF neurons co-expressing ERβ is around 30% to 40% in the middle and caudal levels of the PVN of both sexes [36]. There may be a species difference in the co-expression pattern as well as within the AVP and OXT neurons.…”
Section: Crf Co-expressing Esr2 Mrna Neurons Are Almost Absent In Thecontrasting
confidence: 58%
See 1 more Smart Citation
“…Considering the low percentage of Esr2/CRF and Esr2/AVP in the parvocellular parts in the current study, further experiments are required to determine the indirect action of estrogens on the HPA through AVP and CRF neurons expressing Esr2. In contrast to this result, in mice, the number of CRF neurons co-expressing ERβ is around 30% to 40% in the middle and caudal levels of the PVN of both sexes [36]. There may be a species difference in the co-expression pattern as well as within the AVP and OXT neurons.…”
Section: Crf Co-expressing Esr2 Mrna Neurons Are Almost Absent In Thecontrasting
confidence: 58%
“…An additional possibility may be the lack of specificity of antibodies for ERβ used in previous studies [35]. Regarding the PVN of mice, Oyola et al reported a relatively low ERβ/AVP co-expression with a sex difference (45% in females versus 11% in males in the caudal PVN) [36,37] using transgenic mice model expressing ERβ identified by enhanced green fluorescent protein. This group also reported a high co-expression of ERβ in OXT neurons (>80% in both sexes) in the PVN.…”
Section: Majority Of Avp Neurons Co-express Esr2 In the Pvn And Son Imentioning
confidence: 99%
“…In male mice, our data did not show any impact of neural ERβ deletion on the integrity of the HPA axis either under basal conditions or following an induced restraint stress. This apparent discrepancy between male mice and rats could be due, at least partly, to the recently reported chemoarchitectural differences in ERβ neurons of the paraventricular nucleus between the two species 32 . Indeed, only a modest number of CRH-cre containing cells were found to express ERβ in male mice by comparison to rats.…”
Section: Discussionmentioning
confidence: 92%
“…OT neurons in the PVN express androgen receptors (Zhou, Blaustein, & De Vries, 1994). However, 85% of OT neurons in the PVN also express ERβ in the rat (Hrabovszky et al, 2004; Suzuki & Handa, 2004) and in mice (Oyola, Thomson, Handa, & Handa, 2017). Interestingly, the ERβ-driven reduction in stress-induced CORT and ACTH levels, and PVN neuronal activation is very similar to that observed following OT treatment (Ochedalski, Subburaju, Wynn, & Aguilera, 2007; Windle et al, 2006, 2004).…”
Section: Gonadal Hormones and Neuropeptidergic Regulation Of The Hpamentioning
confidence: 99%